Determining the Effects of the Organizational Commitment on Contextual Performance: A Correlational Study with Nurses - KÃ–ROÄžLU KABA, Nagihan; SarÄ±oÄŸlu Kemer, AyÅŸegÃ¼l (Advances in Nursing & Midwifery, 2022)
Abstract Introduction: This study aimed to determine the effects of the organizational commitment levels of nurses on their contextual performance. Methods: This descriptive and correlational study was conducted in a university hospital with 331 nurses the east of Türkiye. The data were collected using The Contextual Performance Scale and The Organizational Commitment Scale. Data obtained from the study were analyzed by using the Statistical Package for Social Sciences (SPSS) for Windows 22.0. Results: The mean total score of nurses’ organizational commitment was moderate at 2.71 ± 0.835. The mean total score of the contextual performance of nurses was at a high level at 3.84 ±0.604. Correlations between the organizational commitment and the contextual performance (r = 0.253; P < 0.001) were significantly positive. The result of multiple regression showed that demographic variables accounted for the contextual performance by 4% (Adj.R2 = 0.04; P = 0.002). In the model-2 was established by adding organizational commitment to demographic variables and was tested. It was noted that independent variables significantly accounted for contextual performance by 7% with a rise of 3% (Adj.R2 = 0.07; P < 0.001). Conclusions: Nurses are moderately committed to their organizations, and they exhibit a high level of contextual performance in their institutions. The results showed only a small proportion of the variance in contextual performance could be explained by demographic variables and organizational commitment. This study can support to extent to which the contextual performance of nurses is affected by organizational commitment can be determined.